2012
DOI: 10.1111/j.1749-6632.2012.06462.x
|View full text |Cite
|
Sign up to set email alerts
|

Becoming musically enculturated: effects of music classes for infants on brain and behavior

Abstract: Musical enculturation is a complex, multifaceted process that includes the development of perceptual processing specialized for the pitch and rhythmic structures of the musical system in the culture, understanding of esthetic and expressive norms, and learning the pragmatic uses of music in different social situations. Here, we summarize the results of a study in which 6-month-old Western infants were randomly assigned to 6 months of either an active participatory music class or a class in which they experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 43 publications
5
57
0
1
Order By: Relevance
“…Discrimination between the two tone sequences would not be helped greatly by abstraction of sequential rules, such as one based on intervals or chunks of two tones. Therefore, our findings lend further support to the idea that passive statistical learning of distributional information is involved in the gaining of musical knowledge (Castellano, Bharucha & Krumhansl, 1984; Kessler, Hansen & Shepard, 1984; Trainor & Trehub, 1992; Tillmann, Bharucha & Bigland, 2000; Bigand & Poulin-Charronnat, 2006; Trainor et al, 2012; Zatorre & Salimpoor, 2013). …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Discrimination between the two tone sequences would not be helped greatly by abstraction of sequential rules, such as one based on intervals or chunks of two tones. Therefore, our findings lend further support to the idea that passive statistical learning of distributional information is involved in the gaining of musical knowledge (Castellano, Bharucha & Krumhansl, 1984; Kessler, Hansen & Shepard, 1984; Trainor & Trehub, 1992; Tillmann, Bharucha & Bigland, 2000; Bigand & Poulin-Charronnat, 2006; Trainor et al, 2012; Zatorre & Salimpoor, 2013). …”
Section: Discussionsupporting
confidence: 83%
“…Cross-cultural research using stimuli as diverse as Western tonal music, traditional North Indian music, or traditional Balinese music shows that participants are more attuned to the statistical distribution of tones in a given music genre if they are familiar with it than if they have had no prior exposure (Castellano, Bharucha & Krumhansl, 1984; Kessler, Hansen & Shepard, 1984). Developmental studies show a more detailed representation of tonal hierarchy, and thus the statistical distribution of tones, with increasing age and music training (Trainor & Trehub, 1992; Trainor et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…For example, 12-month-olds listen attentively to classical music played with the original instrumentation intended by the composer or a modified arrangement identified as ''baby'' music showing no preferential attention to either (Merkow & CostaGiomi, 2014). They also display undifferentiated attention to instrumental music played with and without expressive nuances (i.e., changes in tempo, dynamics, and timbre) (Trainor, Marie, Gerry, Whiskin, & Unrau, 2012). Similarly, research with young children has shown that three-to six-years-olds show no preferential attention to novel lullabies and children's songs played in various vocal or instrumental renditions (Sims & Cassidy, 1997) and listen attentively to recorded music in laboratory and natural settings for remarkably long periods of time (Sims & Cassidy, 1997;Sims, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…This enhancement can occur even in infancy: infants who participated in “active engagement” music classes for 6 months had larger and earlier cortical responses to a piano note compared to infants who participated in “passive” music classes (Trainor, Marie, Gerry, Whiskin, & Unrau, 2012). School-age children who have consistently practiced a musical instrument for at least 5 years not only have better scores on the Hearing in Noise Test (HINT; Nilsson, Soli, & Sullivan, 1994), but also have brainstem responses to speech that are more resistant to the degradative effects of noise than nonmusicians (Strait, Parbery-Clark, Hittner, & Kraus, 2012).…”
Section: Auditory Trainingmentioning
confidence: 99%